The Impact Of The Implementation Of The Abc Cost Accounting System On Improving The Financial Management Decisions In Private Hospitals Operating In Jordan To Achieve Sustainable Development Goals - Tayseer Ali Khalaf i Al-Moman; Nehad Ibrahim Abd Alfatah Ineizeh; Fawwaz Ali Taha Ababneh; Montaser Khalid Hamdan (Editora Alumni In, 2025)
Non Indexed Publication (Tier 4)